Integrated crop‑livestock systems in the Cerrado region - Vilela, Lourival; Martha Junior, Geraldo Bueno; Macedo, Manuel Cláudio Motta; Marchão, Robélio Leandro; Guimarães Júnior, Roberto; Pulrolnik, Karina; Maciel, Giovana Alcantara (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to analyze the benefits and the potential prospects of integrated crop‑livestock systems in the process of crop and pasture intensification in the Cerrado, and to point out the main information gaps about the system. The main benefits of crop‑livestock integration are: improved chemical, physical and biological properties of the soil; reduction of diseases, pests and weed outbreaks occurrence; higher crop and animal productivity; and risk reduction due to diversification of activities. However, the adoption of the crop‑livestock system is still low, probably due to the greater complexity of the system. Concentrating efforts on the factors that limit the system’s adoption is strategic for new studies. The search for better soil cover for the no tillage system, through forage grasses, can boost the adoption of integrated crop-livestock in the Cerrado. It is expected that the adoption of integrated crop‑livestock systems improve the socioeconomic and environmental sustainability of the farm and of its region of influence.